Activities of Marine Industries in the Russian Sector of the Caspian Sea in the Context of Modern Transformations in Eurasia - Nikolay W. GONTAR (Communications of International Proceedings, 2020)
Modern Eurasia is developing under the influence of a number of unifying projects of the countries of Eurasia itself and external actors to it. In 2015, Russia put forward a project of the Eurasian Economic Union (EAEU). At the same time, the idea of ​ ​ a "shift to the east" was put forward in Russia (the orientation of politics towards closer relations with the countries of the East of Eurasia). In addition, Russia proposed the integration of the EAEU and the Chinese project "One Belt-One Road", including through the North-South corridor through the Caspian Sea. The article explores Russia's strategy in the Caspian Sea, strengthening its ties on the continent and the development of the Caspian regions of Russia. The development of key sectors of the regions of the Caspian Sea (oil and gas production, shipbuilding, fishing) involves an expansion of the industry structure and an increase in its efficiency. It is also planned to improve the institutional conditions for the movement of goods along the North-South corridor, the creation of a fleet, navigation conditions and a single tariff policy for the effective operation of the sea route within the corridor. The SWOT analysis of Russia's implementation of its Eurasian priorities in the Caspian Sea reveals the strengths of the process (geographical location, developed marine complex, proximity to the countries of the region), as well as its weaknesses (inefficiency of specialization industries, limited markets, logistics problems), as the basis for the formation of Russian strategies in the Caspian Sea.
Keywords: Eurasia; Caspian Sea; Russia; Marine Industries.